Pengaruh Penerapan Pembelajaran Daring Terhadap Hasil Belajar Matematika Ditinjau Dari Kemandirian Belajar Mahasiswa - Heny Sri Astutik; Abdul Rahman; Nurwati Djam’an (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Muhammadiyah Sinjai, 2024)
This study aims to find out Are student mathematics learning outcomes in solving problems for students who have high learning independence better than those who have moderate learning independence, are student mathematics learning outcomes in solving questions for students who have high learning independence are better than those who have low learning independence and whether the mathematics learning outcomes of students in solving problems for students who have moderate learning independence are better than those who have low learning independence. This research is a quasi-experimental study with a 2 x 3 factorial design. The population of this research is all students of the mathematics education study program in the even semester of the 2020/2021 academic year. Samples were taken by random sampling. The instruments used in data collection were learning independence questionnaires and learning achievement tests in solving questions in the form of descriptions. Before Questionnaires and tests are used for data collection before being tested to determine validity and reliability. Hypothesis testing using anava two different cell lines, with a significance level of 5%. Previously, the average balance test and prerequisite tests were carried out involving the normality test and homogeneity test. The average balance test uses the t test while the normality test uses the Liliefors test which concerns the normality of the experimental group, control group, independence high learning, moderate learning independence and low learning independence. The homogeneity test uses the Barlett test which concerns learning strategies and learning independence